2003
DOI: 10.1021/bp025560b
|View full text |Cite
|
Sign up to set email alerts
|

Engineering mRNA Translation Initiation to Enhance Transient Gene Expression in Chinese Hamster Ovary Cells

Abstract: To increase transient expression of recombinant proteins in Chinese hamster ovary cells, we have engineered their protein synthetic capacity by directed manipulation of mRNA translation initiation. To control this process we constructed a nonphosphorylatable Ser(51)Ala site-directed mutant of eIF2alpha, a subunit of the trimeric eIF2 complex that is implicated in regulation of the global rate of mRNA translation initiation in eukaryotic cells. Phosphorylation of eIF2alpha by protein kinases inhibits eIF2 activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 48 publications
2
17
0
Order By: Relevance
“…Different metabolic engineering strategies have been designed since to reduce production bottlenecks and improve the specific productivity of mammalian host cell lines or the quality of the product. Most successful examples include (i) transcription engineering using trigger-inducible expression systems (Schlatter and Fussenegger, 2003), (ii) translation engineering consisting of improving ribosomal entry and translationinitiation (Underhill et al, 2003;Umaña et al, 1999), (iii) glycoengineering improving the ADCC activity of therapeutic antibodies (Prati et al, 2002), (iv) controlled proliferation technology which redirects metabolic energy from cell growth to product formation (Fussenegger et al, 1998) and (v) anti-apoptosis engineering which is based on ectopic expression of survival genes (Ishaque and Al-Rubeai, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Different metabolic engineering strategies have been designed since to reduce production bottlenecks and improve the specific productivity of mammalian host cell lines or the quality of the product. Most successful examples include (i) transcription engineering using trigger-inducible expression systems (Schlatter and Fussenegger, 2003), (ii) translation engineering consisting of improving ribosomal entry and translationinitiation (Underhill et al, 2003;Umaña et al, 1999), (iii) glycoengineering improving the ADCC activity of therapeutic antibodies (Prati et al, 2002), (iv) controlled proliferation technology which redirects metabolic energy from cell growth to product formation (Fussenegger et al, 1998) and (v) anti-apoptosis engineering which is based on ectopic expression of survival genes (Ishaque and Al-Rubeai, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…2). Different transfection reagents induce different levels of cytotoxicity in terms of impeded cell growth rate and a drop in viability (our own unpublished observations), as well as the inhibition of protein synthesis (Underhill et al, 2003). Notably, transfection stress can be reduced through process or cell engineering optimization (Johari et al, 2015;Macaraeg et al, 2013;Majors et al, 2008).…”
Section: Transfection Stress and Variabilitymentioning
confidence: 95%
“…A key factor is eukaryotic translation initiation factor-2 (Eif2), which inhibits translation initiation when phosphorylated, and activates initiation in the unphosphorylated form [62]. Underhill et al [63] found that transient overexpression of a mutant form of Eif2, which cannot be phosphorylated, increased the rate of protein synthesis (determined from the extent of [ 35 S] methionine incorporation) in CHO cells.…”
Section: Diamonds In the Roughmentioning
confidence: 99%